WOMEN IN THE QUR’ANIC COSMIC (MURTAḌĀ MUṬAHHARĪ’S INTERPRETATION OF WOMEN IN THE QUR’AN) - Muaffa, Ali; Dewi, Ajeng Indira; Hisyam, Muh. Fathoni; Azizah, Imroatul; Kusuma, Yuanda; Nurkhaeriyah (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
The background for this research stems from a lack of studies on the Murtaḍā Muṭahharī’s paradigm and interpretation of women in the Qur’an. The purpose of this study is to present Murtaḍā Muṭahharī’s ideas on women from the perspective of the Qur’an. Additionally, it aims to neutralize and reduce biased opinions about women and encourage more research on the views of scholars who hold a moderate-progressive paradigm regarding women and their relationships with men. The main source used in this study is Muṭahharī’s work entitled "The Rights of Women in Islam". The research method employed was library research, with a philosophical approach. Two results of this study: firstly, according to Muṭahharī’s comprehensive paradigm of the relationship between men and women, the Quran treats men and women equally as human beings while acknowledging their differences. This influences the rights and responsibilities assigned to each gender. Secondly, the study focused on Muṭahharī’s perspective on women in the Quran. He believed that a woman (Hawa) was not created from a part of a man’s (Adam) body but rather from the same essence as a man. Women have the same spiritual potential as men towards Al-Ḥaq (Allah swt.) and their role is not to serve men, but to work alongside them as partners.